The Efficacy of Organic Zinc Amino Acid Complex(AvailaZn®) on Growth Performance and Immunity of Pangasius Catfish (Pangasianodon hypophthalmus) - Jintasataporn, Orapint; Ward, Terry; Kattakdad, Supalug (Aquacultura Indonesiana, 2014)
The efficacy of organic zinc amino acid complex(AvailaZn®) on growth performance and immunity of Pangasius catfish (Pangasianodon hypophthalmus) was assigned in CRD with  4 treatments and 5 replicates. The treatments  were control with inorganic zinc 100 ppm (T1) and the other two treatments of zinc 100 ppm at different proportion of inorganic zinc : organic zinc  70:30 (T2) and 40:60(T3) and the treatment of only organic zinc 50 ppm (T4; 50% of control). Pangasius catfish with average weight of  209  g. were stocked in 1,000 liter fiber tanks at the density of 15 fishes per tank and fed treatment diets 3% of  body  weight  twice daily for three months. The results indicated that there were statistical difference (p<0.05) on growth performance in term of body weigh and specific growth rate of  Pangasius catfish fed diet supplemental organic zinc at different levels were higher (P<0.05) than group of inorganic control(T1). The specific growth rate were 0.89, 1.20, 1.16 and 1.27 %/ in T1, T2, T3 and T4, respectively. Feed  conversion ratio were not significantly different(p=0.08) and protein efficiency ratio also were not significantly different(p=0.09). White blood cell count, serum protein, immunoglobulin (IgM), hemoglobin, and super oxide anion in group of zinc amino acid complex were better (p<0.05) than group of inorganic control(T1).  Therefore, using zinc amino acid complex(AvailaZn®) in Pangasius catfish diet can enhance catfish growth performance (p<0.05) and decrease zinc level in the catfish diet by 50% of using inorganic zinc. Supplementation zinc amino acid complex(AvailaZn®) in Pangasius catfish diet is recommended at the level of 50 ppm for organic mineral and 100 ppm for the proportion of organic and inorganic 70:30 ppm.